Recombinant Human Bone Morphogenetic Protein-2 in Posterolateral Spinal Fusion: What's the Right Dose? - Martin Franz Hoffmann; Clifford Barry Jones; Debra Lynn Sietsema (Asian Spine Journal, 2016)
Study DesignSingle center retrospective cohort analysis.PurposeThe goal was to evaluate the influence of varying amount of recombinant human bone morphogenetic protein 2 (rhBMP-2) per level on fusion rates and complications in posterolateral spinal fusions.Overview of LiteraturerhBMP-2 has been utilized for lumbar posterolateral fusions for many years. Initial rhBMP-2 recommendations were 20 mg/level of fusion. Dose and concentration per level in current studies vary from 4.2 to 40 mg and 1.5 to 2.0 mg/mL, respectively. Variable fusion and complication rates have been reported.MethodsPatients (n=1,610) undergoing instrumented lumbar spinal fusion (2003–2009) with utilization of rhBMP-2 were retrospectively evaluated. Patient demographics, body mass index (BMI), comorbidities, number of levels, associated interbody fusion, and types of bone void filler were analyzed. Fusions rates and nonunions were subdivided into number of levels and amount of rhBMP-2 used per level.ResultsPatients (n=559) were evaluated with 58.5% females having an average age of 63 years, BMI of 31 kg/m2. Number of levels fused ranged from 1 to 8. rhBMP-2 averaged 7.3 mg/level (range, 1.5–24 mg/level) based upon length of collagen sponge in relation to length of fusion levels. Patients with non-union formation had lower rhBMP-2 dose per level (p=0.016). A significant difference in non-union rate was found between patients undergoing fusion with <6 mg/level compared to those with >6 mg/level (9.1% vs. 2.4%, χ2=0.012). No significant differences were noted between 6–11.9 mg/level and ≥12 mg/level. No threshold was found for seroma formation or bone overgrowth.ConclusionsPrevious recommendation of 20 mg/level of rhBMP-2 is more than what is required for predictable fusion rates of 98%. No dose related increase of infection, seroma formation, and bone overgrowth has been found. In order to provide variable dosing and cost reduction, industry generated rhBMP-2 kit size should be optimized.